2007
DOI: 10.1128/jb.01618-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Act Promoter in Myxococcus xanthus

Abstract: Mutations within the ؊12 and ؊24 elements provide evidence that the act promoter is recognized by sigma-54 RNA polymerase. Deletion of the ؊20 base pair, which lies between the two conserved elements of sigma-54 promoters, decreased expression by 90%. In addition, mutation of a potential enhancer sequence, around ؊120, led to an 80% reduction in act gene expression. actB, the second gene in the act operon, encodes a sigma-54 activator protein that is proposed to be an enhancer-binding protein for the act opero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 74 publications
(74 reference statements)
1
19
0
Order By: Relevance
“…3 A-C suggest that transcription of the nla6, nla28, and actB operons is also subjected to autoregulation; Nla6-DBD, Nla28-DBD, and ActB-DBD were capable of binding to fragments containing the promoter regions of the nla6, nla28, and actB operons, respectively. These findings are consistent with previous work showing that expression of genes in the actB operon is reduced in an actB mutant (34). They are also consistent with the data in Fig.…”
Section: Preaggregation and Aggregation Ebp Genes Are Expressed Insupporting
confidence: 83%
“…3 A-C suggest that transcription of the nla6, nla28, and actB operons is also subjected to autoregulation; Nla6-DBD, Nla28-DBD, and ActB-DBD were capable of binding to fragments containing the promoter regions of the nla6, nla28, and actB operons, respectively. These findings are consistent with previous work showing that expression of genes in the actB operon is reduced in an actB mutant (34). They are also consistent with the data in Fig.…”
Section: Preaggregation and Aggregation Ebp Genes Are Expressed Insupporting
confidence: 83%
“…We also showed that the mutations in the putative Nla6 enhancer in the nla28 promoter reduce its in vivo activity during development. It is noteworthy that previous experimental analyses indicate that the actB, asgE, nla6, and nla28 operons use 54 promoter elements (13,40,47), which are the targets of EBP-mediated regulation. In addition, the remaining promoters that were positive for Nla6 DBD binding contain sequences that are good matches to the 54 promoter consensus (14).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the positive feedback, there is a progressive increase in the cell surface level of Csignal. The five proteins of the act operon increase expression of the csgA gene (Gronewold and Kaiser 2007). At the start of development, there are few C-signal molecules per cell.…”
Section: C-signaling and Developmentmentioning
confidence: 99%